An azo-phenol derivative probe: colorimetric and "turn-on" fluorescent detection of copper(ii) ions and pH value in aqueous solution. Issue 33 (10th April 2017) - Li, Yanchun; Han, Xiaojun; Song, Yan
Abstract : The optical properties of a novel, rhodamine-based derivative, synthesized by reacting rhodaminehydrazide and an azo-phenol derivative in ethanol, were investigated in ethanol–water solution. Abstract : The optical properties of a novel, rhodamine-based derivative, synthesized by reacting rhodaminehydrazide and an azo-phenol derivative in ethanol, were investigated in ethanol–water solution. The novel sensor displayed selectivity for Cu 2+ ions, as evidenced by a colourless to dark red colour change, which was characterized using UV visible spectroscopy and which also allowed visual detection of Cu 2+ . In contrast, selectivity towards pH was determined from changes in the absorption spectra in the micromolar range. This represents the first reported rhodamine-based sensor capable of detecting both Cu 2+ and pH using two different modes. In addition, the rhodamine-based sensor has been successfully applied in the biomedical research field to the fluorescence imaging of Cu 2+ in HeLa cells.